Modeling the long-term antibody response of a hepatitis E vaccine. Issue 33 (7th August 2015) - Chen, Shu; Zhou, Zi; Wei, Fei-Xue; Huang, Shou-Jie; Tan, Zhong; Fang, Ya; Zhu, Feng-Cai; Wu, Ting; Zhang, Jun; Xia, Ning-Shao
<x xml:space="preserve">Abstract</x> Highlights This is the first report regarding the long-term antibody response modeling of HEV 239 vaccine. Two models used in this study were fit well using the anti-HEV IgG data from 1278 baseline seronegative vaccine recipients. The HEV 239 vaccine is predicted to provide from 8 years to near life-long persistence of anti-HEV IgG above detectable levels. Model predictions in this study are based on conservative mathematical assumptions.